2017
DOI: 10.18632/oncotarget.18395
|View full text |Cite
|
Sign up to set email alerts
|

AKT can modulate the in vitro response of HNSCC cells to irreversible EGFR inhibitors

Abstract: Epidermal growth factor receptor (EGFR) is overexpressed in up to 90% of head and neck squamous cell carcinoma (HNSCC) tumors. Cetuximab is the first targeted (anti-EGFR) therapy approved for the treatment of HNSCC patients. However, its efficacy is limited due to primary and secondary resistance, and there is no predict biomarkers of response. New generation of EGFR inhibitors with pan HER targeting and irreversible action, such as afatinib and allitinib, represents a significant therapeutic promise. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
2
28
1
Order By: Relevance
“…Our data are consistent with previous studies showing the benefit of PI3K-and EGFR-inhibitor combination therapies (Rebucci et al, 2011;Young et al, 2013;D'Amato et al, 2014;Lattanzio et al, 2015;Michmerhuizen et al, 2016;Anisuzzaman et al, 2017;Silva-Oliveira et al, 2017) and also extend that work by discovering that PI3K inhibitors are much more effective in combination with irreversible than reversible EGFR inhibitors in HNSCC. In prior work comparing the classes of EGFR-targeting monotherapies in this cancer type, preclinical data demonstrated that irreversible EGFR inhibitors are superior to other EGFR-targeting agents, including cetuximab (Ather et al, 2013;Silva-Oliveira et al, 2017) and reversible inhibitor gefitinib (Young et al, 2015). Similarly, previous work has shown that the addition of ERBB2-targeting antibodies pertuzumab (Erjala et al, 2006) or trastuzumab (Kondo et al, 2008) to gefitinib enhances its efficacy in HNSCC cell lines; however, our findings demonstrated that the broader specificity of irreversible inhibitors alone cannot explain these differences in sensitivity, as administering ERBB2-inhibitor CP-724714 with gefitinib and HS-173 did not enhance drug effects (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data are consistent with previous studies showing the benefit of PI3K-and EGFR-inhibitor combination therapies (Rebucci et al, 2011;Young et al, 2013;D'Amato et al, 2014;Lattanzio et al, 2015;Michmerhuizen et al, 2016;Anisuzzaman et al, 2017;Silva-Oliveira et al, 2017) and also extend that work by discovering that PI3K inhibitors are much more effective in combination with irreversible than reversible EGFR inhibitors in HNSCC. In prior work comparing the classes of EGFR-targeting monotherapies in this cancer type, preclinical data demonstrated that irreversible EGFR inhibitors are superior to other EGFR-targeting agents, including cetuximab (Ather et al, 2013;Silva-Oliveira et al, 2017) and reversible inhibitor gefitinib (Young et al, 2015). Similarly, previous work has shown that the addition of ERBB2-targeting antibodies pertuzumab (Erjala et al, 2006) or trastuzumab (Kondo et al, 2008) to gefitinib enhances its efficacy in HNSCC cell lines; however, our findings demonstrated that the broader specificity of irreversible inhibitors alone cannot explain these differences in sensitivity, as administering ERBB2-inhibitor CP-724714 with gefitinib and HS-173 did not enhance drug effects (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, pharmacologic inhibition or siRNA knockdown of AKT resulted in improved sensitivity to afatinib and allitinib (a second irreversible EGFR inhibitor) in HN13 cells (Silva-Oliveira et al, 2017). The need to suppress AKT phosphorylation in responses to PI3K 1 EGFR drug combinations is supported by studies of both EGFR-targeting antibodies (Benavente et al, 2009;Rebucci et al, 2011) and reversible inhibitors (Benavente et al, 2009;Rebucci et al, 2011;Young et al, 2013;Silva-Oliveira et al, 2017). In lungcancer models, irreversible EGFR inhibitors have sustained reductions in EGFR phosphorylation and an improved ability to decrease effector AKT phosphorylation compared with reversible inhibitors (Kwak et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After washing with PBS (1 mL/well, twice), cells were lysed with lysis buffer (70 µL/well); Tris 50 mM pH 7.6-8, NaCl 150 mM, EDTA 5 mM, Na 3 VO 4 1 mM, NaF 10 mM, Na pyrophosphate 10 mM, and 1% NP-40 and supplemented with a cocktail of inhibitors (DTT-Dithiothreitol, leupeptin hemisulfate, aprotinin, PSMF-Phenylmethylsulfonyl fluoride, and EDTA) for 1 h, followed by centrifugation (4 • C, 15 min, 13,000 rpm). The protein concentration was determined by Bradford reagent [50]. All samples (untreated and Coronarin d-treated cells) were total cellular protein (20 µg protein/sample) and separated by electrophoresis on 10% gradient gels in SDS-PAGE and blotted onto nitrocellulose membranes by electroblotting in transfer buffer (Trizma base, glycine, distilled water, and methanol).…”
Section: Western Blotting Assaymentioning
confidence: 99%
“…However, only a minority of patients derive long-term benefit from anti-EGFR mAbs (5,6). Resistance mechanisms to EGFR inhibition for HNSCC remain unclear (7), although multiple mechanisms of acquired and de novo resistance have been suggested (8,9), paving the way for trials of combination strategies (7,10,11). Optimal HNSCC patient selection for anti-EGFR-based therapy remains a challenge (7).…”
Section: Introductionmentioning
confidence: 99%